2017
DOI: 10.1111/bph.13845
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic lymphocytes and atherosclerosis: significance, mechanisms and therapeutic challenges

Abstract: Cytotoxic lymphocytes encompass natural killer lymphocytes (cells) and cytotoxic T cells that include CD8+ T cells, natural killer (NK) T cells, γ, δ (γδ)-T cells and human CD4 + CD28À T cells.These cells play critical roles in inflammatory diseases and in controlling cancers and infections. Cytotoxic lymphocytes can be activated via a number of mechanisms that may involve dendritic cells, macrophages, cytokines or surface proteins on stressed cells. Upon activation, they secrete pro-inflammatory cytokines as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 237 publications
(249 reference statements)
0
32
2
1
Order By: Relevance
“…T cells constitute a variable but substantial proportion of the immune cell population in the atherosclerotic plaque and are significant drivers of the inflammatory responses that underlie atherosclerosis 1 , 3 . CD4 + T cells are the predominant T cell subset in atherosclerotic lesions of Apolipoprotein E-deficient ( Apoe − / − ) mice.…”
Section: Introductionmentioning
confidence: 99%
“…T cells constitute a variable but substantial proportion of the immune cell population in the atherosclerotic plaque and are significant drivers of the inflammatory responses that underlie atherosclerosis 1 , 3 . CD4 + T cells are the predominant T cell subset in atherosclerotic lesions of Apolipoprotein E-deficient ( Apoe − / − ) mice.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al found a high proportion of CD8+ cells and a low proportion of CD4+ cells according to the AHI in children suffering from OSAS [10]. CD8+ cells constitute the T cell subpopulation which contributes to the formation of atherosclerotic lesions [11]. We previously reported an elevated proportion of lymphocytes with Fas expression in patients with lung cancer and in COPD [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Their work is complemented by the review from Foks and Kuiper (), where the authors discuss the therapeutic potential to control atherosclerosis through targeting a large variety of co‐stimulatory and inhibitory immune checkpoint proteins. In addition, the role of cytotoxic lymphocytes such as NK cells, CD8 + T‐cells, NK T‐cells, γδ T‐cells and human CD4 + CD28 − T‐cells in the development of atherosclerosis and unstable atheromas is reviewed (Kyaw et al ., ).…”
Section: Nomenclature Of Targets and Ligandsmentioning
confidence: 97%